CFD simulation of the steam gasification of millimeter-sized char particle using thermally thick treatment - Chen, Tao; Ku, Xiaoke; Lin, Jianzhong (Combustion and flame, 2020)
A detailed char gasification model is developed using a multiphase Eulerian–Lagrangian algorithm and thermally thick treatment. The model is first validated by both gasification and combustion experiments of a millimeter-sized char particle. Temperature and mass loss histories as well as the particle morphology evolution correspond well with the existing results. Then the steam gasification of a 5 mm char particle is simulated and detailed physical and chemical conversion processes inside the particle are explored. During gasification, three distinct layers, i.e., the outer ash layer, the intermediate layer and the core layer, are identified based on the intraparticle porosity distribution. Simulation results show that the highest H2O and CO2 mass fractions locate in the ash layer, while the intermediate and core layers contain the highest H2 and CO mass fractions, respectively. Moreover, effects of several parameters are also explored. It is found that the Stefan flow caused by the mass transfer plays a key role in determining the diffusion and convection behavior during gasification. The strength of the Stefan flow in the intermediate layer appears to be two orders of magnitude smaller than that of the inflow and has an influence on the shifting from a kinetically-controlled mode to a diffusion-controlled mode. In addition, the char consumption rate in the intermediate layer increases with an increase in steam mass fraction, gasification temperature and inflow velocity while it decreases with increasing particle diameter. Meanwhile, the char consumption rate caused by CO2 is much smaller than that due to steam.